(6-8i)(6+8i)=

Simple and best practice solution for (6-8i)(6+8i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6-8i)(6+8i)= equation:


Simplifying
(6 + -8i)(6 + 8i) = 0

Multiply (6 + -8i) * (6 + 8i)
(6(6 + 8i) + -8i * (6 + 8i)) = 0
((6 * 6 + 8i * 6) + -8i * (6 + 8i)) = 0
((36 + 48i) + -8i * (6 + 8i)) = 0
(36 + 48i + (6 * -8i + 8i * -8i)) = 0
(36 + 48i + (-48i + -64i2)) = 0

Combine like terms: 48i + -48i = 0
(36 + 0 + -64i2) = 0
(36 + -64i2) = 0

Solving
36 + -64i2 = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-36' to each side of the equation.
36 + -36 + -64i2 = 0 + -36

Combine like terms: 36 + -36 = 0
0 + -64i2 = 0 + -36
-64i2 = 0 + -36

Combine like terms: 0 + -36 = -36
-64i2 = -36

Divide each side by '-64'.
i2 = 0.5625

Simplifying
i2 = 0.5625

Take the square root of each side:
i = {-0.75, 0.75}

See similar equations:

| 3(t-5)-t=7 | | 2x+2y=2809.30 | | 2(5x-6)=4[x-3x+30] | | 100x^2-21=110 | | 4(3x-9)-5=4(x-5)+27 | | 4y^3+27y^2+27=0 | | 27y^2+27=0 | | 3-4*6+3= | | 4(3x-8)-5=4(x-5)+15 | | (11x+26)-3= | | Y^6+9y^4-4y^3+27y^2+27=0 | | -7(2c+5)=(c-6) | | 8y-9=12y+15 | | 5x-(2x+4)=14 | | x^2-5x-2.25=0 | | Y=(3x+8)(x-9) | | 6+(3x-4)-(7x+11)= | | 8(7x-6)=27 | | x+20=5x+8 | | x*0.022=1 | | 12y-13=7y+12 | | 4-23=8x-6-7x | | 2(3x)+5x=770 | | 2x+11=21-3x | | 10x=20.2 | | 80=1.8+32 | | 8+2(x-8)=10-6(x-3) | | 7(x-2)+2=7x-2(2-x) | | (6-2x)*5=(x-3)*8 | | f(3x+1)=5*x+2 | | 6-2x*5=x-3*8 | | -(z+9)+(2z+1)=-4(z+1) |

Equations solver categories